2016
DOI: 10.21474/ijar01/2070
|View full text |Cite
|
Sign up to set email alerts
|

Disc Prolapse Awareness Among Population in Taif- Saudi Arabia.

Abstract: Background:-Prolapsed Intervertebral Disc (PID) is a major cause of disability in developing countries. Aims: The study aimed to investigate the awareness of disc prolapse (DP) among people in Taif city, Saudi Arabia. Settings and Design:-Descriptive cross section study was conducted in different areas in Taif(Taif University, schools, Mall and hospitals)during the period from September to December 2015. Methods and Material:-Thisstudy was done to a sample of 1034 people living in Taif were selected randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
(11 reference statements)
1
6
1
Order By: Relevance
“…2017 in Taif city who recorded high knowledge level regarding disc herniation and its risk factors. As for diagnostic measures, the current study findings were similar to that recorded by Taif city study[2] as both recorded poor knowledge regarding how to diagnose disc herniation health condition. Moussa et al .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…2017 in Taif city who recorded high knowledge level regarding disc herniation and its risk factors. As for diagnostic measures, the current study findings were similar to that recorded by Taif city study[2] as both recorded poor knowledge regarding how to diagnose disc herniation health condition. Moussa et al .…”
Section: Discussionsupporting
confidence: 85%
“…The questionnaire was in Arabic language obtained from previous study which conducted in Taif city. [2] In the previous questionnaire, we added two questions about treatment and a question about symptoms of disc herniation. Content validity for the questionnaire was done as it was reviewed by three experts for any modification of corrections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the findings in Taif study are inconsistent to our study in which they reported that most of the participants did not know the gold standard imaging as the method of choice to diagnose the disease, alsomost of the participants did not know the preventive methods and the analgesics that can be used to relieve symptoms of the disease. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…The study showed good knowledge about the disease itself, however, participants had a lack of knowledge about risk factors and preventive methods of disc herniation. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%